2017
DOI: 10.1093/cid/cix653
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcal Disease Worldwide for Pregnant Women, Stillbirths, and Children: Why, What, and How to Undertake Estimates?

Abstract: Group B Streptococcus is associated with multiple adverse pregnancy outcomes, yet previous epidemiology and interventions have mainly focused on neonatal invasive disease in high-income settings. We describe the rationale and approach for the first worldwide estimates of all relevant outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 53 publications
(64 reference statements)
0
100
0
Order By: Relevance
“…Group B streptococcus and S pneumoniae present specific opportunities for interventions, for example by maternal immunisation. [141][142][143] Our results show sub-regional geographical variation in the distribution of specific bacterial pathogens between and within regions (table 2). One key finding was the higher number of studies from southern Africa reporting group B streptococcus infections compared with other regions, although the prevalence of infections did not differ significantly across regions.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Group B streptococcus and S pneumoniae present specific opportunities for interventions, for example by maternal immunisation. [141][142][143] Our results show sub-regional geographical variation in the distribution of specific bacterial pathogens between and within regions (table 2). One key finding was the higher number of studies from southern Africa reporting group B streptococcus infections compared with other regions, although the prevalence of infections did not differ significantly across regions.…”
Section: Discussionmentioning
confidence: 57%
“…In spite of this potential bias, true geographical differences in disease epidemiology or regional differences in virulence and host susceptibility cannot be ruled out. 141,145 Variability in group B streptococcus disease might also reflect differences in case ascertainment (especially among home births), before antibiotic treatment, blood culture or lumbar puncture practices, variability in laboratory capacity, and the quality of microbiological investigations. 145 A South African study 146 reported significant variation in neonatal invasive group B streptococcus disease incidence by province with differential access to health care, poor laboratory capacity, and varying diagnostic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Group B Streptococcus colonization and vertical transmission can cause fetal infection and stillbirth as a direct result of toxin-induced cytolysis [ 7 , 8 ]. Group B Streptococcus is estimated to account for 15% of all infection related stillbirths globally [ 9 ] and Africa harbor 73.68% of the estimated GBS caused stillbirth [ 10 ]. Other factors associated with stillbirth include: higher maternal age, residence, lower economic status, lower education level, poor antenatal care (ANC) uptake, antepartum hemorrhage, essential hypertension, pre-eclampsia, obstetric complication during labour, preterm delivery, low birth weight, and fetal mal-presentation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even in high-resource countries where the incidence of confirmed neonatal sepsis is relatively low (1–5 cases per 1,000 live births 3,5,9,11,12 ) and all such infants would receive treatment, approximately 40% will either die or suffer major developmental disabilities 13 . Although reported incidence rates of neonatal sepsis from low-resource countries are generally higher 1416 , cases are likely underascertained owing to many factors, including a lack of access to care, poor quality care, and a lack of adequate laboratory services 16,17 . In one review of community-based studies from low- and middle-income countries, incidence rates ranged from 49 to 170 cases per 1,000 live births across 11 studies 16 .…”
Section: Introductionmentioning
confidence: 99%